2018
DOI: 10.1002/tox.22528
|View full text |Cite
|
Sign up to set email alerts
|

Naringenin (4,5,7‐trihydroxyflavanone) suppresses the development of precancerous lesions via controlling hyperproliferation and inflammation in the colon of Wistar rats

Abstract: Colon cancer is a world-wide health problem and one of the most dangerous type of cancer, affecting both men and women. Naringenin (4, 5, 7-trihydroxyflavanone) is one of the major flavone glycoside present in citrus fruits. Naringenin has long been used in Chinese's traditional medicine because of its exceptional pharmacological properties and non-toxic nature. In the present study, we investigated the chemopreventive potential of Naringenin against 1,2-dimethyhydrazine (DMH)-induced precancerous lesions, tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 61 publications
13
34
0
Order By: Relevance
“…Methyl free radical generated by metabolism of DMH cause accumulation up of hydroxyl radical or hydrogen peroxide that may contribute to lipid peroxidation or MDA . Lipid peroxidation is a known marker of oxidative stress in colon toxicity and that remarkable elevation in the level of MDA, a lipid peroxidation product, was observed after DMH treatment . Our results corroborated with the previous studies which reveled marked decrease in MDA levels after zingerone treatment (Figure ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Methyl free radical generated by metabolism of DMH cause accumulation up of hydroxyl radical or hydrogen peroxide that may contribute to lipid peroxidation or MDA . Lipid peroxidation is a known marker of oxidative stress in colon toxicity and that remarkable elevation in the level of MDA, a lipid peroxidation product, was observed after DMH treatment . Our results corroborated with the previous studies which reveled marked decrease in MDA levels after zingerone treatment (Figure ).…”
Section: Discussionsupporting
confidence: 92%
“…Recent studies report the role of ROS production including singlet oxygen, hydroperoxides, H 2 O 2 , and O 2 − in origination of DMH toxicity . The present study demonstrated the oxidative damage in colon led by excessive ROS production on DMH exposure.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Quercetin glucosides are also present in Bayo Victoria beans and are related to cytotoxicity of HepG2, PC-3 and HT-29 cancer cell lines (Pan, Zheng, & Ho, 2018). In addition, Bayo Victoria beans have naringenin, which is related to antiproliferative effects in animal models, suppressing the development of cancerous lesions (Rehman et al, 2018).…”
Section: Cell Viabilitymentioning
confidence: 99%